1968
DOI: 10.1136/bmj.3.5619.653
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-acting Synthetic Corticotrophin in Hypersensitive Asthmatics and Normal Subjects

Abstract: Summary: The synthetic polypeptide depot-tetracosactrin (Synacthen-Depot) was given to nine steroidtreated asthmatic patients hypersensitive to animal corticotrophin. Eight had a satisfactory increase in plasma and urinary 17-hydroxycorticosteroids (17-OHCS). The remaining patient had been shown previously to have adrenal suppression. None of the patients developed allergic reactions to depot-tetracosactrin, and seven have been receiving regular injections of the polypeptide twice weekly for the past eight mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…4. The plasma 11-OHCS 'profile' after a single intramuscular injection of 0 5 mg depot tetracosactrin was similar to that previously described (Nelson, Neill, Montgomery, MacKay, Sheridan, and Weaver, 1968;El Shaboury, 1968;Nuki and others, 1970). Plasma 1 1-OHCS levels rose significantly at 30 minutes, were maximal after 8 hours and still significantly raised after 24 but not after 48 hours.…”
Section: Red Blood Cell Studiessupporting
confidence: 85%
See 2 more Smart Citations
“…4. The plasma 11-OHCS 'profile' after a single intramuscular injection of 0 5 mg depot tetracosactrin was similar to that previously described (Nelson, Neill, Montgomery, MacKay, Sheridan, and Weaver, 1968;El Shaboury, 1968;Nuki and others, 1970). Plasma 1 1-OHCS levels rose significantly at 30 minutes, were maximal after 8 hours and still significantly raised after 24 but not after 48 hours.…”
Section: Red Blood Cell Studiessupporting
confidence: 85%
“…Tetracosactrin in doses as small as 3 ,cg/h has been shown to elicit a maximal rise in plasma 1 1-OHCS (Landon, James, Cryer, Wynn, and Frankland, 1964). Injection of 0 5 mg depot tetracosactrin results in a maximal rise in 1 1-OHCS which is similar to that induced by 40 units of ACTH gel (Nelson and others, 1968;El Shaboury, 1968) but the adrenocortical stimulation is more prolonged. Maximal stimulation of cortisol and corticosterone can be obtained with a dose of 1250,ug, but the threshold for stimulation of aldosterone is much higher (Fraser, Brown, Chinn, Lever, and Robertson, 1969).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another patient we had a similar, though less alarming, reaction to depot injections with swellings at the site of every previous depot injection. ' CONCLUSIONS Our studies have confirmed previous suggestions (Nelson et al, 1968;el-Shaboury, 1968;Galvao-Teles, Burke, and Russell Fraser, 1971;Westerhof et al, 1972) that the use of depot tetracosactrin injections, albeit for a prolonged time, is usually successful in reactivation of the adrenal glands and in providing more satisfactory control of asthma in those whose condition was severe enough to warrant long-term oral steroid administration. We failed to produce satisfactory adrenal response in only six out of 41 patients, even though initial testing had sometimes suggested complete adrenal suppression.…”
Section: Difficulties With Tetracosactrinsupporting
confidence: 89%
“…However, this preparation may produce painful local reactions if given subcutaneously or sometimes intramuscularly (Besser et al, 1967;Nelson et al, 1968;Treadwell and Dennis, 1969), and this seems to be due to the contained zinc complexes. Occasionally generalized allergic reactions after tetracosactrin depot occur though in general it can be used in patients who are hypersensitive to animal ACTH (El-Shaboury, 1968;Jensen and Sneddon, 1969). …”
Section: Introductionmentioning
confidence: 99%